Upaya Manajemen Sekolah dalam Menghadapi Hambatan Sarana Prasarana Pendidikan - Aline Nikita; Nadya Petricia Lubis; Sifah Fauziah (Universitas Palan, 2023)
. In an educational organization or school, it cannot be separated from its relationship with learning media or commonly called facilities and infrastructure. Facilities and infrastructure aim as a place to carry out learning activities and increase student learning motivation. Therefore, facilities and infrastructure are very important to advance and develop the productivity of educational institutions. In addition, the management of infrastructure is one of the things that must be considered so that it can help encourage student achievement and achieve the goals of educational organizations. Facilities and infrastructure have a very important urgency to increase student learning productivity. However, the implementation of facilities and infrastructure management in schools does not always go well. There are problems or obstacles that need to be resolved and overcome so as not to interfere with the learning process. Factors that hinder the management of facilities and infrastructure in schools usually arise from internal and external factors. Therefore, school management needs to make various efforts to overcome these obstacles. This study aims to determine the efforts of school management in overcoming barriers to educational infrastructure. From the method used, namely the qualitative method with literature study techniques, it produces an elaboration which shows that school management efforts in overcoming obstacles to facilities and infrastructure are planning, organizing, procuring, inventorying, distributing, maintaining, eliminating, and monitoring and evaluating.